Differential equations for engineers - Xie, Wei-Chau, 1964- (New York : Cambridge University Press, 2010)
'This book presents a systematic and comprehensive introduction to ordinary differential equations for engineering students and practitioners'--Provided by publisher.
'This book presents a systematic and comprehensive introduction to ordinary differential equations for engineering students and practitioners. Mathematical concepts and various techniques are presented in a clear, logical, and concise manner. Various visual features are used to highlight focus areas. Complete illustrative diagrams are used to facilitate mathematical modeling of application problems. Readers are motivated by a focus on the relevance of differential equations through their applications in various engineering disciplines. Studies of various types of differential equations are determined by engineering applications. Theory and techniques for solving differential equations are then applied to solve practical engineering problems. Detailed step-by-step analysis is presented to model the engineering problems using differential equations from physical principles and to solve the differential equations using the easiest possible method. Such a detailed, step-by-step approach, especially when applied to practical engineering problems, helps the readers to develop problem-solving skills'--Provided by publisher.
Includes index.
Includes bibliographical references and index.
Keywords: Differential equations; Engineering mathematics